RELATIONSHIP CHARACTERISTICS OF WELDING WORKERS ON VISUAL LOANS IN THE WELDING INDUSTRY, PONTIANAK CITY - Iskandar Arfan; Rochmawati Rochmawati; Irvan Ardiansyah Zulmianto (Journal of Industrial Hygiene and Occupational Health, 2019)
Vision (visual acuity) is a measure of how far the details of an object can caught by the eye so that the vision can be called an important eye physiology. Preliminary observations to 10 welding workers showed that 10 workers or 100% experience visual complaints with VFI more than 0.4 and many workers who complain of a sharp decrease in vision. This research is analytic observation research with cross sectional method. In this study the population was 91 respondents with Purposive Sampling sampling method so that the total sample was 74 respondents. Chi-Square test results on the discipline variable of  PPE use obtained p - value (0.001) PR=283.500(CI 95%= 30.060-2673.699), length of work obtained p - value (0.001) PR=24.600 (CI 95%= 6.961-86.935), length of exposure obtained p - value (0.001) PR=30.000 (CI 95%= 7.491-120.138), exposure distance obtained p - value (0.001) PR=24.667 (CI 95%= 6.824-89.157), and daily habits obtained p - value (0.001) PR=23.611 (CI 95%= 6.021-92.591) on sharpness vision so that it can be concluded that all variables have a significant relationship to sharp vision (vision ). Advive to the Manpower Office to make policies related to occupational safety and health for welding, fostering,and supervising workers in promoting and preventing efforts to prevent occupational diseases, especially those related to providing information that is expected to provide understanding to owners and welding workers on how to conduct safe welding and conduct periodic monitoring of occupational safety and health conditions to the welding industry and provide guarantees of safety to workrs so as to avoid occupational diseases.Keywords: Sharp Vision (Vision), Characteristics of Welding Workers, Welding Industry